Sagittal Reconstruction and Clinical Outcome Using Traditional ACDF, Versus Stand-alone ACDF Versus TDR: A Systematic Review and Quantitative Analysis. Issue 19 (1st October 2019) - Katsuura, Yoshihiro; York, Philip J.; Goto, Rie; Yang, Jingyan; Vaishnav, Avani S.; McAnany, Steven; Albert, Todd; Iyer, Sravisht; Gang, Catherine Himo; Qureshi, Sheeraz A.
Abstract : Study Design: Systematic review. Objective: To determine the difference in postoperative sagittal alignment when single level cervical radiculopathy or myelopathy is treated with an anterior cervical discectomy and fusion (ACDF) using a structural graft and plate, a stand-alone ACDF, or a total disc arthroplasty (TDR). We also wanted to determine if postoperative sagittal alignment impacted clinical outcomes in this patient population. Summary of Background Data: Although there are several accepted techniques for interbody reconstruction during single level anterior cervical surgery, little is known on the impact of any of them on segmental and regional sagittal alignment. Methods: A systematic review of the literature was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines of the PubMed, Embase, and Cochrane databases. Only studies which contained pre and postoperative C2–7 Cobb angles as well as Neck Disability Index (NDI) scores following single level traditional ACDF with plate and cage, stand-alone ACDF, or TDR with at least 1 year follow up were included. Results: There were 12 publications that fulfilled the inclusion criteria with a total of 658 patients. Cluster regression analysis showed no difference between treatment arms at each respective time-point or in the overall change in NDI from preoperative to postoperative ( P = 0.88). Cluster regression analysis showed no difference between treatment arms at each respective time point or in the overall change in lordosis from pre-op to post-op ( P = 0.93). Conclusion: This review provides evidence that while NDI scores improved across all devices, there was no significant difference in NDI improvement or C2–7 Cobb angle change between single level traditional ACDF, stand-alone ACDF, or TDR. Although TDR has not been considered a lordosis producing operation, our investigation shows it does not differ significantly in sagittal profile from other cervical fusion techniques. Moreover, we show that the NDI score improved, regardless of device implanted. Level of Evidence: 1 Abstract : Though Neck Disability Index (NDI) scores improved across devices for anterior cervical discectomy and fusion (ACDF) using a structural graft and plate, a stand-alone device, or a total disc arthroplasty (TDR), there was no significant difference in NDI improvement or C2–7 Cobb angle change between single level traditional ACDF, stand-alone ACDF, or TDR. TDR has not been considered a lordosis producing operation; however, our investigation shows it does not differ significantly in sagittal profile from other cervical fusion techniques.